Double Degree Transnational Curriculum: University Internationalization Efforts in Malaysia with British Universities - Raya, Moch. Khafidz Fuad (UIII Press, 2023)
Higher Education (HE) is central to advancing a nation's civilisation. In the modern context, HE has been polarised into a different practice discourse. This is the effect of globalisation which orients the neoliberal economic paradigm. This current resulted in a massive change in orientation (reform) of HE in Malaysia, which forced policymakers to internationalise HE. One of them is the transnational double degree program. British universities are considered the most suitable partners for this program due to several factors, such as the historical trajectory of British colonialism and imperialism towards Malaysia. This study uses a qualitative approach with ethnographic and documentary methods. Using the theory of